Er-Miao-Fang Extracts Inhibits Adipose Lipolysis and Reduces Hepatic Gluconeogenesis via Suppression of Inflammation - Zhao, Wenjun; Feng, Xin; Liu, Baolin; Xian, Jiechen; Zhang, Ning (Frontiers in Physiology, 2018)
High-fat-diet (HFD) feeding induces adipose dysfunction. This study aims to explore whether the Traditional Chinese Medical prescription Er-Miao-Fang could ameliorate adipose dysfunction and prevent hepatic glucose output. Short-term HFD feeding induced adipose lipolysis accompanied with enhanced hepatic glucose output in mice. Adipose lipolysis is initiated by cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) signaling. Oral administration Er-Miao-Fang inhibited inflammation in adipose tissue by dephosphorylation of JNK and reducing TNF-α and IL-1β production, and thus preserved phosphodiesterase 3B (PDE3B) induction, contributing to preventing cAMP accumulation. As a result, from suppression of PKA activation, Er-Miao-Fang reduced fatty acids and glycerol release from adipose tissue due to the inhibition hormone-sensitive lipase (HSL). By blocking the traffic of fatty acids and inflammatory mediators from adipose tissue to the liver, Er-Miao-Fang attenuated hepatic cAMP/PKA signaling by protecting phosphodiesterase 4B (PDE4B) induction from inflammatory insult, and thereby reduced hepatic glucose production by suppression of hepatic glucagon response in HFD-fed mice. In conclusion, Er-Miao-Fang prevented adipose lipolysis by suppression of inflammation, contributing to reducing excessive hepatic glucose output. These findings present a new view of regulating gluconeogenesis and provide the guiding significance for the regulation of multi-link targets with Traditional Chinese Medicine.